1996
DOI: 10.2519/jospt.1996.23.4.245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Kinesthetic Deficits Indicative of Balance Control in Gymnasts With Unilateral Chronic Ankle Sprains

Abstract: he central nervous sys tem uses a dynamic combination of sensory inputs from the vestibular, somatosensory, and visual svstem to control balance. Information from all three sensory systems, although somewhat redundant, enables the central nervous system's recognition and control of the body's orientation in space, relative orientation of body segments, and relative interaction of body center of gravity and center of pressure (16). The central nervous system varies the weight assigned to each sensory input acco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
55
0
6

Year Published

2002
2002
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(65 citation statements)
references
References 6 publications
3
55
0
6
Order By: Relevance
“…Keith et al (3) observaram que entorses são comuns entre ginastas, devido às altas cargas de impacto exercidas pelas acrobacias, executadas com grande potência, altura e compostas por movimentos rotacionais, como também mencionado por Marshall et al (19) . Além disso, Forkin et al (20) descrevem que a força de reação do solo é da ordem de oito a 18 vezes o peso corporal no momento da aterrissagem. Nesses eventos, como explicado por Souza e Almeida (21) , o impacto sobre estruturas articulares é maior que a capacidade de absorção dos músculos, agredindo o tecido que as compõe.…”
Section: Discussionunclassified
“…Keith et al (3) observaram que entorses são comuns entre ginastas, devido às altas cargas de impacto exercidas pelas acrobacias, executadas com grande potência, altura e compostas por movimentos rotacionais, como também mencionado por Marshall et al (19) . Além disso, Forkin et al (20) descrevem que a força de reação do solo é da ordem de oito a 18 vezes o peso corporal no momento da aterrissagem. Nesses eventos, como explicado por Souza e Almeida (21) , o impacto sobre estruturas articulares é maior que a capacidade de absorção dos músculos, agredindo o tecido que as compõe.…”
Section: Discussionunclassified
“…For example, deficits in joint movement sense, as measured by asking the subject to report if movement occurred or not, have been well documented. 10,14,15 Specifically, subjects with functionally unstable ankles or a history of ankle sprains have greater impairment of movement sense than uninjured subjects. Additionally, inversion active joint reposition sense, or the ability of subjects to actively reproduce a target angle, is impaired in subjects with ankle instability.…”
Section: Freemanmentioning
confidence: 99%
“…7 Hertel 8,9 first identified the overlapping nature of mechanical and functional instability and later noted that individuals with CAI have a continuum of deficits associated with the use of afferent stimuli, reflexive responses, and efferent motor control. Investigators have identified specific deficits in proprioception, 10,11 peroneal reaction time, 12,13 and postural control 14,15 in individuals with CAI. Alterations in lower extremity kinematics during gait [16][17][18][19] and jump landings 20,21 also are evident in individuals with CAI, whereas strength deficits are controversial.…”
mentioning
confidence: 99%